Comparative Activity of Several Antimicrobial Agents against Nosocomial Gram-Negative Rods Isolated across Canada - Shelley R Scriver; Canadian Antimicrobial Resistance Study Group; Donald E Low (Canadian Journal of Infectious Diseases)
In 1992, a surveillance study was performed in Canada to determine the susceptibility of nosocomial Gram-negative rods to several wide spectrum antimicrobials. Consecutive isolates from 10 institutions, as well as additional strains of selected species of Enterobacteriaceae that are known to possess the Bush group 1 beta-lactamase, were tested for susceptibility to 12 antimicrobials. Third-generation cephalosporin resistance was found to be as high as 29% in Enterobacter cloacae that possesses the Bush group 1 beta-lactamase and less than 4% in those isolates not possessing this enzyme. Cefepime equalled or exceeded the activity of the third-generation cephalosporins against the species of Enterobacteriaceae that demonstrated resistance to the third-generation cephalosporins.